2008
DOI: 10.1093/schbul/sbn033
|View full text |Cite
|
Sign up to set email alerts
|

Attributional Style in Delusional Patients: A Comparison of Remitted Paranoid, Remitted Nonparanoid, and Current Paranoid Patients With Nonpsychiatric Controls

Abstract: Many studies have found that people experiencing persecutory delusions have a marked tendency to use external-personal attributions when establishing the causes of negative events. Although nonclinical populations also tend to attribute negative events to external causes, those causes are typically believed to be universal in nature, rather than personal. The central goal of the present study was to investigate whether individuals with remitted persecutory delusions would display this external-personal bias re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 34 publications
6
35
0
1
Order By: Relevance
“…In line with previous research, we found that schizophrenia patients had deficits in all four examined domains of social cognition [39,40,41,42,43]. According to our hypothesis, the performance in the social-cognitive tests explained almost half of the variance of the ego disturbance score.…”
Section: Discussionsupporting
confidence: 92%
“…In line with previous research, we found that schizophrenia patients had deficits in all four examined domains of social cognition [39,40,41,42,43]. According to our hypothesis, the performance in the social-cognitive tests explained almost half of the variance of the ego disturbance score.…”
Section: Discussionsupporting
confidence: 92%
“…2 Fueling interest is a convergence of data indicating that individuals with schizophrenia are impaired in social cognitive abilities, including facial affect perception, 3 recognition of emotional prosody, 4 and theory of mind (ToM), 5 as well as evidence indicating that individuals with persecutory ideation tend to show attribution biases such as blaming others, rather than situations, for negative events. [6][7][8] Growing evidence also indicates that impairments in social cognition may precede onset of the disorder 9,10 and are present early in the illness. [11][12][13] Interest in social cognition in schizophrenia has also increased because it contributes to a variety of realworld outcomes, such as social competence, community functioning, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the tendency to blame other people rather than circumstances or situational factors for negative events (i.e. personalizing attributional bias), is well established in paranoid patients [19]. It has been also hypothesized that emotion recognition (ER) deficits, through negative misperceiving of social-emotional cues, participate in the occurrence of paranoid elaborations [20] and social withdrawal/isolation [21], that often accompany schizophrenia.…”
Section: Medicinski Podmladakmentioning
confidence: 99%